Factors Driving Marketing Mix and Customer Relationship Management Affecting Performance of Outdoor Billboard Businesses in Thailand - Chandee, Kritsada; Chinantdej, Norapol; Paopun, Natsapan; Chiarakul, Tanyamai (Ph.D. in Social Sciences Journal, 2021)
In objectives of this research article are to study, (1) the congruence of the driving factors model, human resource management technology and leadership affecting the marketing mix, customer relationship management (CRM) and the performance of outdoor billboard businesses in Thailand with empirical data. (2) the factors of technology, Human Resource Management (HRM) and leadership influencing the marketing mix. (3) the factors of technology, HRM, leadership and the marketing mix influencing CRM. (4) examines the factors of technology, HRM, leadership, marketing mix and CRM influencing the performance of the businesses under study. The researcher conducted quantitative research to collect data from 662 administrators. The statistics used in data analysis were frequency distribution, percentage, mean, and standard deviation. The techniques of confirmatory factor analysis and the structure equation model were also employed. Findings are as follows: The analysis of the structural equation model was in congruence with the empirical data at a good level. The test of the influence of factors in each aspect found the following: Technology exhibited, Human Resource Management exhibited and Leadership exhibited a positive influence on the marketing mix and a positive influence on Customer Relationship Management. By all factors and customer relationship management exhibited a positive influence on business performance.